2007
DOI: 10.1007/s10903-007-9113-3
|View full text |Cite
|
Sign up to set email alerts
|

Body Weight and Length of Residence in the US Among Chinese Americans

Abstract: Background-It has been shown that as immigrants' length of residence increases, so does their weight. However, little is known about factors associated with weight status among Chinese Americans, one of the fastest growing immigrant populations in the US.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 24 publications
4
16
1
Order By: Relevance
“…We had hypothesized that anthropometric measures would mediate an association between acculturation and HOMA because of previously observed associations between acculturation and BMI in studies of Asian immigrants. 3,4,28,29 In our study group, however, although anthropometric measures were strong predictors of HOMA, acculturation did not predict anthropometry, and the association between acculturation and HOMA in less-educated women persisted even when anthropometry was taken into account. Because in our previous work acculturation was associated with more dietary changes among less educated women, 10,11 we also hypothesized that diet might mediate an association between acculturation and insulin resistance.…”
Section: Acculturation and Insulin Resistance -Tseng And Fangcontrasting
confidence: 70%
See 1 more Smart Citation
“…We had hypothesized that anthropometric measures would mediate an association between acculturation and HOMA because of previously observed associations between acculturation and BMI in studies of Asian immigrants. 3,4,28,29 In our study group, however, although anthropometric measures were strong predictors of HOMA, acculturation did not predict anthropometry, and the association between acculturation and HOMA in less-educated women persisted even when anthropometry was taken into account. Because in our previous work acculturation was associated with more dietary changes among less educated women, 10,11 we also hypothesized that diet might mediate an association between acculturation and insulin resistance.…”
Section: Acculturation and Insulin Resistance -Tseng And Fangcontrasting
confidence: 70%
“…1,2 Weight gain after migration is common as well, 3,4 but the increase in diabetes occurs despite a generally low prevalence of overweight and obesity in this population. 1,2,5 The rapid change in risk upon migration suggests a role for acculturation-related lifestyle factors.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, data derived from the 2000 National Health Interview Survey indicated that among various immigrant subgroups, number of years of residence in the USA was associated with higher BMI. 37 Yeh et al 38 examined baseline data collected from a multi-stage probability sample of Chinese Americans living in two communities in New York City. Length of residence in the USA positively correlated with BMI status, particularly among adults who had been residing in the USA for 16 years or more.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to study morbidity differences according to gender, ethnic background and age 61,62 . Cultural preferences, such as media usage 63 , and other indicators are often used to measure acculturation instead of, or in addition to, length of residence in the host country. Figure 2 shows several variables that may mediate the impact of immigration on health.…”
Section: Sub-saharan Africansmentioning
confidence: 99%